Online Games and Their Effects on Student Behavior in Extracurricular Activities - Charisma Fikri; Darwati Darwati; Taruddin Taruddin; Ahmad Suryadi (Sekolah Tinggi Agama Islam Solok Nan Indah, 2025)
Online games are very popular among students in Indonesia today and have a significant impact on their behaviour. These games use the internet, allowing players to interact with one another from different locations. This is the main reason why online games are so popular. Technological advances should function as tools and media to support student learning in schools, families, and communities. The purpose of this study was to identify students’ online gaming habits, their behaviour in extracurricular activities, and the negative effects of online gaming on learning time at school. The research employed a qualitative approach in the form of a case study. Data were collected from the principal, supervising teachers, and students who participated in extracurricular activities such as basketball, music, and scouting at Senior High School through observation, interviews, and documentation. The results of the analysis revealed three major impacts of online games on student behaviour. First, students have been playing online games since 2019, with the most common games being Mobile Legends, Free Fire, and Player Unknown’s Battle Grounds. Second, students’ behaviour while playing online games includes feelings of enjoyment, excitement, challenge, and frustration. Third, the positive impacts of online games include easier interaction, stress relief, and improved teamwork, while the negative impacts include neglecting schoolwork, using foul language, and engaging in fights. The results of this study can serve as initial data for further research on this issue in different contexts and settings.